Pharmacotherapeutic options for treatment of insomnia - Singh, Jarnail; Singh, Janardhan (International Journal of Basic & Clinical Pharmacology, 2017)
Insomnia is a functionally debilitating condition characterized by repeated difficulty with sleep initiation, maintenance, or quality of sleep despite adequate opportunity. If left untreated, it can lead to increased risk of depression, poor memory, reduced concentration, poor work performance, and poor general health. Although gamma-aminobutyric acid (GABA) ergic system remains the primary target for current insomnia treatments, still over-the-counter (OTC) drugs with a different mechanism of action are in use for insomnia. OTC drugs target only one of the parallel arousing systems and may improve mild insomnia for a short period. They are not likely to improve symptoms over long-term and thus are not the ideal agents. Studies evaluating the efficacy and outcomes of sedative hypnotic drugs beyond 1 year are limited. Currently, there are no Food and Drug Administration approved pharmacotherapies for insomnia in the pediatric population. Increased understanding of complex neuronal networks involved in sleep and wake has led to the development of new drugs for insomnia that target a diverse range of receptors. Potential agents under investigations are targeting mechanisms and pathways including histamine (H1) receptor, melatonin, and orexin receptors. This review describes the pharmacotherapy of insomnia and the drugs under development for the treatment of insomnia.